Search for heavy long-lived multicharged particles in proton-proton collisions at √s=13 TeV using the ATLAS detector - Aaboud, Morad; Anders, Christoph; Andrei, George Victor; Antel, Claire; Baas, Alessandra Edda; Bolz, Arthur; Brandt, Oleg; Britzger, Daniel; Dunford, Monica; Franchino, Silvia; Geisler, Manuel Patrice; Hanke, Paul; et al. (Physical review, 2019)
A search for heavy long-lived multicharged particles is performed using the ATLAS detector at the LHC. Data with an integrated luminosity of 36.1 fb−1 collected in 2015 and 2016 from proton-proton collisions at √s=13 TeV are examined. Particles producing anomalously high ionization, consistent with long-lived massive particles with electric charges from |q|=2e to |q|=7e, are searched for. No events are observed, and 95% confidence level cross-section upper limits are interpreted as lower mass limits for a Drell-Yan production model. Multicharged particles with masses between 50 and 980-1220 GeV (depending on their electric charge) are excluded.
Im Titel steht der Buchstabe s unter dem Wurzelsymbol
*ATLAS Collaboration: M. Aaboud, C. Anders, G.V. Andrei, C. Antel, A.E. Baas, A. Bolz, O. Brandt, D. Britzger, M. Dunford, S. Franchino, M.P. Geisler, P. Hanke, J. Jongmanns, A. Kugel, H. Meyer zu Theenhausen, F. Napolitano, D.I. Narrias Villar, M. Sahinsoy, H.-C. Schultz-Coulon, T. Spieker, R. Stamen, P. Starovoitov, S. Suchek, S. Weber, M. Wessels, X. Yue [und 2916 weitere]
Gesehen am 22.07.2019